Climate change in layer poultry farming: Impact of heat waves in region of Bastos, Brazil - Lamarca, D. S.F. [UNESP]; Pereira, Danilo Florentino [UNESP]; Magalhães, M. M. [UNESP]; Salgado, D. D. [UNESP] (FapUNIFESP (SciELO), 2018)
The region around the municipality of Bastos, state of São Paulo, accounted for about 7% of Brazilian egg production in 2015. In 2012, it experienced a heat wave that resulted in the death of approximately 500,000 hens, according to information released at the time. Considering the impact of heat waves on layer mortality, the objective of this study was to analyze how heat waves impact the layer farming in the region of Bastos, considering the climate change scenarios forecasted by the IPCC for the next years. This study was conducted in three stages: i) analysis of the IPCC reports to understand climate change scenarios; ii) analysis of historical temperature data in the region of Bastos; iii) analysis of how climate change, through heat waves, may impact layer mortality in this region. All the IPCC scenarios indicate that both average temperature and the number of extreme events, such as heat waves, are expected to increase. Historical data showed that since the mid-1980s, maximum temperature has increased, as well as the frequency, intensity and duration of heat waves. The association of layer mortality due to heat waves with the IPCC climate change forecasts for that region indicates a trend of increasing layer mortality in egg production operations which sheds are not equipped with air conditioning.
Keywords: Egg production; Extreme event; IPCC; Laying hens; Mortality